Perceptions about care in adults with intellectual disabilities in an Ar-gentine day center - Carmona Gallego, Diego (2022)
Introduction: This article starts from the perspective that affirms that care is more than a task and alludes to ways of linking each person with himself, with others and with ecosystems. In this way, the assumption that all people have knowledge about care and can care is supported. Main goal: To analyze the perceptions about the care presented by adults with intellectual disabilities who attend a day center in the central region of Argentina, based on their own experiences and meanings. Method and technique: The study is framed in the qualitative paradigm, from the Grounded Theory approach. This article presents the results of 10 in-depth interviews and 2 reflective conversation circles (focus groups) developed between the months of February and May 2022, with 10 adults of different genders and ages who attend a day center, dedicated to their social and labor inclusion. [Continue reading in the article]